Analysis of viral RNA and apoptotic cells in bursae following infection with vaccine and very virulent strains of infectious bursal disease virus - Kong, Lih Ling; Omar, Abdul Rahman; Bejo, Mohd Hair; Ideris, Aini; Seow, Heng Fong (Universiti Putra Malaysia Press, 2004)
Previously we have shown that the very virulent (vv) infectious bursal disease virus (IBDV) UPM94/273 and UPM91/61 have significantly distinct pathogenicity and genetic profiles. In this study, a SYBR‚ Green I based real-time reverse transcriptase reaction assay was developed to measure viral RNA in the bursae of chickens infected with IBDV. A linear relationship was observed between the amount of input viral RNA and the threshold values for IBDV-specific product over five log10 dilutions. The viral RNA level following infection with UPM94/273 was significantly higher at day 1 and 2 post-inoculation (p.i) compared to UPM97/61 infected chickens. However, chickens infected with UPM97/61 had significantly higher numbers of bursal cells undergoing apoptosis compared to UPM94/273 infected chickens. In both groups the number of apoptotic cells and viral RNA levels peak at day 3 p.i. This study indicates UPM97/61 and UPM94/273 have different efficiency of replication and percentage of apoptotic cells in bursae during the acute phase of IBDV infection.